Effect on Color Change Vital Bleaching Agents Applied for Different Durations After Orthodontic Debonding: A Comparative Clinical Case Series - Şeyda SAÇAN; Elif Pınar BAKIR2 (Necmettin Erbakan Universitesi Dis Hekimligi Dergisi (NEU Dent J), Necmettin Erbakan, 2026)
Tooth discoloration following orthodontic treatment is a common esthetic concern. This clinical case series evaluated the effect of different application durations of a high-concentration in-office bleaching agent on tooth color change after orthodontic debonding. Twelve patients were allo-cated into three groups according to bleaching duration: 20, 40, and 60 minutes. A 40% hydro-gen peroxide gel formulation (Opalescence Boost PF, Ultradent, USA) was applied under stand-ardized isolation conditions. Color measurements were conducted before and after treatment using a spectrophotometer (VITA Easyshade V) and recorded as CIE L*a*b* values. Whitening effectiveness was determined by calculating ΔE values, and postoperative sensitivity was assessed using the Visual Analog Scale (VAS). Mean ΔE values were 5.70, 8.19, and 10.68 in the 20, 40, and 60 minute groups, respectively, indicating a duration-dependent increase in whitening effect. Postoperative sensitivity also increased with longer application times, although it remained transi-ent and clinically tolerable. The perceptibility threshold for color change (ΔE>3.6) was exceeded in most cases, supporting the clinical effectiveness of the procedure. Within the limitations of this small case series, longer application times were associated with greater whitening efficacy and higher sensitivity.